Two new cichild species Neolamprologus (Teleostei: Cichlidae) from Lake Tanganyika, East Africa - Verburg, Piet; Bills, Roger (Zootaxa, 2007)
Two new cichlid species, Neolamprologus walteri sp. nov. and N. chitamwebwai sp. nov., from the Bangwe peninsula (Tanzania), on the east coast of Lake Tanganyika, are described. Both species belong to the N. savoryi species complex, characterised by a lunate tail with long filaments. Neolamprologus chitamwebwai and N. walteri are highly stenotopic species, restricted to rocky habitat. They occur sympatrically with each other and with two other species of the complex but occupy different microhabitats. Neolamprologus walteri lives in large numbers in sheltered areas with rubble substrate whereas N. chitamwebwai occurs in much lower numbers on more exposed parts of the rocky shores, with large boulders, lower sedimentation rates, coarser sediment, and higher visibility. The two new species although closely related, show clear ecological differentiation. Evidence of ecological differentiation between closely related sympatric cichlids is rare in literature. Closely related sympatric cichlids in the large African lakes (with literature mainly referring to Lake Victoria and Lake Malawi) have been suggested to differ little in diet and habitat use, which has encouraged the idea that cichlid species can coexist without niche partitioning. Our paper provides a different perspective with cichlids from Lake Tanganyika.